ANALISIS PERBANDINGAN IMPLEMENTASI KURIKULUM 2013 DAN KURIKULUM MERDEKA BELAJAR DI SDN 182 PEKANBARU - Salsa Tria Diva; Zaka Hadikusuma Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the world of education, the term curriculum has always developed in line with developments in educational theory and practice. The change in curriculum from 2013 to the independent learning curriculum resulted in many changes starting from planning, implementation and evaluation in learning. This research uses qualitative research with a narrative approach. The sources of this research are school principals, educators and students at SDN 182 Pekanbaru. Data was collected using observation, interviews and documentation methods. Using data analysis techniques, namely data reduction, data presentation, drawing conclusions and verification. The results of this research show that the comparison of learning planning, namely the 2013 curriculum, consists of the Annual Program, Semester Program, syllabus, Core Competencies, Basic Competencies, Competency Achievement Indicators, and Learning Implementation Plans, while the independent learning curriculum consists of the annual program, semester program, Flow of Learning Objectives , Learning Achievements, Learning Objectives, Indicators of Achievement of Learning Objectives and teaching modules. Comparison of learning implementation in the 2013 curriculum using a thematic approach while the independent learning curriculum uses a subject approach. Comparison of learning evaluation in the 2013 curriculum using authentic assessment consisting of aspects of attitudes, knowledge and skills and using Minimum Completeness Criteria, while the independent learning curriculum uses formative and summative assessments and using Learning Goal Achievement Criteria.